Genital Secretion HIV RNA Shedding in HIV-Positive Patients on Ritonavir-Boosted Protease Inhibitor Monotherapy or Standard Combination ART: A Cross-Sectional Sub-Study from the PIVOT Trial. Issue 1 (January 2020) - Arenas-Pinto, Alejandro; Stöhr, Wolfgang; Khoo, Saye; Clarke, Amanda; Beeching, Nicholas; Warwick, Zoe; Lee, Vincent; Else, Laura; Wiggins, Rebecca; Ferns, Bridget; Nastouli, Eleni; Dunn, David; et al.
Background: Protease inhibitors (PI) have relatively low penetration into the genital tract, raising concerns about the potential for genital HIV RNA shedding in patients taking PI-based regimens, particularly PI monotherapy (PI-mono). Methods: We measured HIV RNA and PI drug concentrations in samples of semen, cervicovaginal and rectal mucosa secretions, and plasma in patients after 48–96 weeks on PI-mono or standard triple therapy. Results: A total of 85 participants were recruited. Of the 43 participants on PI-mono (70% on darunavir [DRV]/ ritonavir [r]), 3 had detectable virus in semen or vaginal secretions (all below quantification limit), and none in rectal mucosa or plasma. Among those taking triple therapy, five had detectable virus in semen or vaginal secretions (HIV RNA >50 copies/ml in one), none in rectal mucosa and one in plasma. The median (IQR) concentration of DRV and atazanavir in semen (659.7 [339–1, 089] and 128.8 [63–368] ng/ml, respectively) and cervico-vaginal samples (2, 768 [312–7, 879] and 1, 836 [359–3, 314] ng/ml, respectively) exceeded their protein adjusted median inhibition concentration (MIC50 ). DRV concentration in rectal secretions showed higher variability compared with concentration in the other sites, with particularly high rectal secretion/blood ratios (median 8.4, IQR 2.6–68.7:1). Conclusions: We found no substantive evidence of HIV shedding in patients taking PI-mono, suggesting that PIs provide adequate control of virus in the genital compartment and are unlikely to lead to ongoing sexual transmission.